How hindrance stress, proactive personality, and the employment relationship atmosphere affect employees’ innovative behavior - Fan, Jianpeng; Fan, Yukun; Yu, Lingli; Man, Shuyu (Frontiers in Psychology, 2022)
Hindrance stress is a stimulus factor in the workplace that has a certain impact on the innovative behavior of employees. Most existing studies focus on the analysis of individual-level factors, ignoring the important role of organizational-level factors. This study uses multiple linear models to empirically analyze the interaction mechanisms among hindrance stress, proactive personality, employment relationship atmosphere, and employee innovative behavior factors in the workplace. This study found the following: (1) Hindrance stress negatively affects employees’ innovative behavior. (2) A proactive personality positively affects employees’ innovative behavior. (3) A proactive personality plays a moderating role in the relationship between hindrance stress and employees’ innovative behavior. (4) The employment relationship atmosphere has a positive impact on employees’ innovative behavior. (5) The employment relationship atmosphere plays a moderating role in the relationship between hindrance stress and employees’ innovative behavior. This study enriches theoretical knowledge in the field of human resources and provides guidance for business managers on the effective encouragement of employees’ innovative behavior.